2006
DOI: 10.1057/palgrave.development.1100287
|View full text |Cite
|
Sign up to set email alerts
|

Technologies of Existence: The indigenous environmental justice movement

Abstract: Dana E. Powell argues that the Indigenous Environmental Justice Movement in North America is resignifying ‘development’ through emerging discourses and practices of ‘environmental justice’. She focuses on the emergence of wind and solar energy technologies in the movement as technologies of existence, challenging a history of biopolitical regimes of natural resource development of indigenous lands and bodies while also proposing an alternative approach to cultivating healthy economies, ecologies, and cultures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In a related theoretical vein, and with Mitchell's (2011) Carbon Democracy as a frequently cited exemplar and inspiration, several contributions here work to integrate attention to materialities, assemblages and “artifactual politics” that has long been advanced by STS—with similar histories too of contestation and evolving synthesis with political economy and political ecology (e.g. Kirsch and Mitchell, 2004; McFarlane and Anderson, 2011 vs Brenner et al, 2011 and Appadurai, 2015, but then Ranganathan, 2015; Demaria and Schindler, 2016; Baker and McGuirk, 2017 and others). In expanding this toolkit for analysis of renewable energy transition, authors contend with such preexisting critiques of these approaches.…”
Section: Key Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a related theoretical vein, and with Mitchell's (2011) Carbon Democracy as a frequently cited exemplar and inspiration, several contributions here work to integrate attention to materialities, assemblages and “artifactual politics” that has long been advanced by STS—with similar histories too of contestation and evolving synthesis with political economy and political ecology (e.g. Kirsch and Mitchell, 2004; McFarlane and Anderson, 2011 vs Brenner et al, 2011 and Appadurai, 2015, but then Ranganathan, 2015; Demaria and Schindler, 2016; Baker and McGuirk, 2017 and others). In expanding this toolkit for analysis of renewable energy transition, authors contend with such preexisting critiques of these approaches.…”
Section: Key Contributionsmentioning
confidence: 99%
“…This rising debate centers around how more just models of the renewable energy transition are conceived, and diverging visions for making renewables live up to their potential as liberatory "technologies of existence" (Powell, 2006). Consistent with much energy democracy organizing to date, alternatives to the kind of large project favored by mainstream investors and governments have often been imagined to lie in local solutions and distributed energy models such as rooftop solar and community energy (see, e.g.…”
Section: Further Directionsmentioning
confidence: 99%
“…55 This characterization holds true in the context of shale gas development on Indigenous lands where Indigenous peoples may be among the first to suffer from local environmental degradation. 56 Environmental justice literature [57][58][59][60][61] has shown that Indigenous peoples are often more vulnerable to the environmental risks related to resource extraction for two main reasons that are described below.…”
Section: Part 2: Water Governance and Environmental (In)justice: Resolving Or Reproducing?mentioning
confidence: 99%
“…First, Indigenous peoples, as well as those marginalized in environmental decision‐making for reasons of race, income, class, culture, age, and gender, bear a disproportionate burden and exposure to risks of industrial development and the associated environmental degradation . This pattern is true worldwide, and Canada is no exception.…”
Section: Part 2: Water Governance and Environmental (In)justice: Resolving Or Reproducing?mentioning
confidence: 99%
“…While EJ principles articulate space for Indigenous Peoples and IEJ movements, explicit cross movement interaction remains understudied due to a lack of emphasis on conceptions of justice that address cultural and political inclusion of Indigenous practices and rights to self-determination (Gilio-Whitaker 2019; Schlosberg 2004). Interconnected with the traditional EJ framework, IEJ promotes a different understanding of justice and environmental protection rooted in sovereignty and the fair and meaningful involvement of Indigenous Peoples (Schlosberg and Carruthers 2010; Vickery and Hunter 2016) to reflect the diversity of Indigenous, Native, and Aboriginal experiences (McGregor 2018; Powell 2006; Whyte 2011).…”
mentioning
confidence: 99%